Effects of HPGR products of mixed magnetite-hematite on subsequent grinding. (17th February 2023) - Guo, Siyao; Zhao, Tonglin; Tang, Hao
Abstract: This research mainly elaborates on the characteristics of the products obtained after grinding for mixed magneto-hematite under conditions of the high-pressure grinding roller (HPGR) and jaw crusher (JC) products as feed. By comparing the relative grindability, liberation degree (LD), work index and pre-selected product indexes of the grinding products, the effect of the HPGR products on the subsequent grinding was discussed. The test results show that the relative grindability and LD of the grinding products obtained from HPGR products as feed is significantly higher than that of JC products, and the energy consumption in the grinding process is significantly reduced. In addition, with the increase of grinding fineness, the LD distribution law of grinding products of different comminution products is normalized. The results of the pre-concentration show that the HPGR as feed can increase the grade and recovery by 2.96 percentage points and 2.12 percentage points, respectively.